PELATIHAN PENGGUNAAN APLIKASI MOODLE SEBAGAI PERSIAPAN MENGHADAPI UJIAN NASIONAL BERBASIS KOMPUTER PADA SMK NEGERI 1 OGAN KOMERING UL - Anggina Primanita; M. Ihsan Jambak; Danny M. Saputra; Rusdi Efendi (Annual Research Seminar (ARS), 2016)
[1]N. H. C. L. B. Gibson, "A case study of a fast track SAP R/3 implementation at Guilbert," Electronic Markets, no. June, pp. 190-193, 1999.[2]R. I. Heroza, "Requirement Modeling for Academic Data Inventory in Faculty of Computer Science Sriwijaya University," in Annual Research Seminar, Palembang, 2015.[3]V. Kumar, B. Maheshwari and U. Kumar, "An Investigation of critical management issues in ERP implementation: empirical evidence from Canadian Organizations," Technovation, vol. 23, pp. 793-807, 2003.[4]A.-m. A. Z. M. Al-Mashari Majed, "Enterprise resource planning A taxonomy of critical factors," European Journal of Operational Research, 2002.[5]C. Larman, Applying UML and Patterns: An Introduction to Object Oriented Analysis and Design and the Unified Process, Prentice Hall, 2004.[6]M. Fowler, UML Distilled: A Brief Guide to the Standard Object Modeling Language, Addison-Wesley Professional, 2003.